Village Community Adaptation to Agricultural Downstreaming - Muhamad Chairul Basrun Umanailo; Varissca Utari Tuharea; Muhtyaningsih Harum Ode Halidu; Marwan Hidayat Lussy; Aswar Muhidin (Utan Kayu Publishing, 2025)
Agricultural downstream innovation in Buru Regency, Maluku, has significant potential to absorb local labor, reduce unemployment, and improve the welfare of rural communities. The region's abundant natural resources should be utilized to support national food security through efficient agricultural processing. This study employed a qualitative method with an explanatory case study approach to examine the causal relationships between variables. Thirty informants were selected purposively from seven villages. Data were collected through in-depth interviews and participant observation, then analyzed thematically using MAXQDA 24.4.1 software. The findings indicate that rural communities are actively adapting to agricultural downstreaming through social and economic strategies, while preserving cultural heritage. This process combines value-added creation, risk management, and social capital utilization. However, for socio-economic resilience to be sustainable, support is needed in the form of technology adoption, resource access, and inclusive social participation. Future policies should strengthen social capital, preserve local values, economic innovation, and community participation. Further research is recommended to explore the impact of value changes, technological barriers, social capital mapping, and a comparison of adaptation models.